Primary Health Care: a strategic framework for the prevention and control of chronic non-communicable disease - Alessandro R. Demaio; Karoline Kragelund Nielsen; Britt Pinkowski Tersbøl; Per Kallestrup; Dan W. Meyrowitsch (Taylor & Francis Group, 2014)
In 2014, chronic, non-communicable diseases (NCDs) represent the leading causes of global mortality and disability. Government-level concern, and resulting policy changes, are manifesting. However, there continues to be a paucity of guiding frameworks for legislative measures. The surge of NCDs will require strong and effective governance responses, particularly in low and middle-income countries. Simultaneously following the 2008 World Health Report, there has recently been renewed interest in Primary Health Care (PHC) and its core principles. With this, has come strengthened support for revitalizing this approach, which aims for equitable and cost-effective population-health attainment. In this light and reflecting recent major global reports, declarations and events, we propose and critique a PHC approach to NCDs, highlighting PHC, with its core themes, as a valuable guiding framework for health promotion and policy addressing this group of diseases.